Hubungan Antara Kecemasan Dengan Kejadian Insomnia pada Mahasiswa Tingkat Akhir di Fakultas Kedokteran Universitas Sam Ratulangi Manado - Paendong, Della; Fitriani; Frans Wantania (Mapalus Nursing Science Journal, 2024)
Background: Anxiety is a mental disorder characterized by feelings of tension, restlessness, and chaotic thoughts. One of the impacts of anxiety is insomnia. Insomnia is the inability to meet sleep needs, both in terms of quality and quantity. Objective: This study aims to analyze the relationship between anxiety levels and the occurrence of insomnia. Method: This study employs a correlational analytical method with a cross-sectional approach. The research was conducted from June 2024 to July 2024 at the Faculty of Medicine, Sam Ratulangi University, Manado, involving students from the Nursing and Dentistry programs, with a sample size of 73 active eighth-semester students. The instrument used the Hamilton Anxiety Rating Scale (HAM-A), and Insomnia Rating Scale (KSBJ-IRS). Results: The Spearman’s Rank Correlation Coefficient test results showed a p-value of <0.038, with a Spearman correlation coefficient of 0.243, indicating a relationship between anxiety and insomnia among final-year students. Conclusion: There is a relationship between anxiety and the occurrence of insomnia in final-year students, where higher levels of anxiety are associated with an increased likelihood of experiencing insomnia. Keywords: Insomnia; Anxiety; Final-year student